Comprehensive somatic genome alterations of urachal carcinoma. Issue 8 (27th March 2017) - Lee, Seungchul; Lee, Jingu; Sim, Sung Hoon; Lee, Yeonghun; Moon, Kyung Chul; Lee, Cheol; Park, Woong-Yang; Kim, Nayoung KD; Lee, Se-Hoon; Lee, Hyunju
Abstract : Background: Urachal cancer is a rare cancer that develops in the urachus. Because of its rarity, standard treatment therapies for urachal cancer are not established, and chemotherapeutic regimens for bladder cancer have been unsuccessful for patients with urachal cancer. Hence, we aim to understand a systematic molecular characterisation of urachal cancer. Methods: We identified somatic single-nucleotide variations (SNVs)/indels and somatic copy number aberrations (SCNAs) in the 17 patients by using whole-exome sequencing (WES) and OncoScan platform (Affymetrix) as follows: tumour-normal paired sequencing (WES, n=10), tumour-only sequencing (WES, n=1; targeted deep sequencing, n=16), and OncoScan (n=17). Results: Our analyses identified 27 genes with somatic SNVs and indels, as well as six genes (APC, COL5A1, KIF26B, LRP1B, SMAD4 and TP53) that were recurrent in at least two patients. By analysing the SCNAs, we found that the extent of chromosomal amplification was highly associated with the patient's cancer stage. Interestingly, 35% (6/17) of the patients had focal DNA amplifications in fibroblast growth factor receptor family genes. The integration of somatic SNVs, indels and SCNAs revealed significant alterations in the mitogen-activated protein kinase signalling pathways. Conclusions: Our genome-wide analysis of urachal cancer suggests that molecular characteristics may be important for the treatment of urachal cancer.